The Role of Extracellular Polymeric Substances in Micropollutant Removal - Melo, Antonio; Quintelas, Cristina; Ferreira, Eugénio C.; Mesquita, Daniela P. (Frontiers in Chemical Engineering, 2022)
In biological wastewater treatment, microorganisms live and grow held together by a slime matrix comprised of extracellular polymeric substances (EPS), forming a three-dimensional microbial structure of aggregates (flocs or granules) and by chemical binding forces. Furthermore, microscopic observations showed that microbial cells within the flocs were cross-linked with EPS, forming a network of polymers with pores and channels. The EPS are typically composed of organic substances such as polysaccharides, proteins, humic acids substances, nucleic acids, and lipids. It has been established that EPS plays an essential role in the flocculation, settling, and dewatering of aggregates. Moreover, in the presence of toxic substances, such as pharmaceutical compounds and pesticides, EPS forms a protective layer for the aggregated biomass against environmental disturbances that might play an important role in the transport and transformation of micropollutants. Some researchers indicated that under toxic conditions, there is an increase of EPS concentrations, which can induce an increase in the size of microbial aggregates. In this contribution, we critically review the available information on the impact of micropollutants on microbial EPS production and the relationship between EPS and microbial aggregate structure. Also, a general definition, composition, and factors that affect EPS production are presented.